Sequential Bayesian Analysis in accounting settings* - AMERSHI, AMIN H.; DEMSKI, JOEL S.; FELLINGHAM, JOHN (Contemporary Accounting Research, 1985)
Abstract. The familiar decision analysis setting in accounting, such as a cost‐volume‐profit analysis setting, is modeled as arising in a “larger” context in which subsequent choice is also contemplated. We then ask when this “larger” context decomposes in a manner such that the immediate problem of interest can be modeled as an expected utility maximization problem that is completely divorced from the subsequent choice problem. Outcome and taste independence conditions are the key ingredients in being able to model the immediate problem as having no link whatever to its successor. Résumé. Le contexte dans lequel les techniques d'analyse de décision comme par exemple l'analyse coĉt‐volume‐profit est utilisée est un cadre d'un modèle élargi qui tient compte du choix subséquent. On se demande en quelles circonstances ce contexte élargi peut‐il se décomposer de façon telle que le problème d'intérêt immédiat en soit un de maximisation complètement séparé du problème du choix subséquent. Le résultat et des conditions d'indépendance de préférence sont les ingrédients clés pour modeler le problème immédiat comme n'ayant aucun lien avec son successeur.